Impact of left ventricular unloading using a peripheral Impella®‐pump in eCPR patients. Issue 3 (25th September 2021) - Gaisendrees, Christopher; Djordjevic, Ilija; Sabashnikov, Anton; Adler, Christopher; Eghbalzadeh, Kaveh; Ivanov, Borko; Walter, Sebastian; Schlachtenberger, Georg; Merkle‐Storms, Julia; Gerfer, Stephen; Carstens, Henning; Deppe, Antje‐Christin; et al.
Abstract: Background: Extracorporeal cardiopulmonary resuscitation (eCPR) is a rapidly growing treatment strategy due to increasing survival rates in selected patients. Additional left ventricular mechanical unloading, using a transfemoral micro‐axial blood pump (Impella® Denver, Massachusetts, USA), might improve patients' outcomes. In this regard, we sought to investigate patients who suffered OHCA (out‐of hospital cardiac arrest) or IHCA (in‐hospital cardiac arrest) with subsequent eCPR via VA‐ECMO (veno‐arterial extracorporeal membrane oxygenation) and concomitant Impella® implantation based on survival and feasibility of ECMO weaning. Methods: From January 2016 until December 2020, 108 patients underwent eCPR at our institution. Data prior to eCPR and early outcome parameters were analyzed comparing patients who were supported with an additional Impella® (2.5 or CP) (ECMO+Impella®, n = 18) and patients without additional (ECMO, n = 90) support during V‐A ECMO therapy. The primary endpoint was in‐hospital mortality; secondary endpoints were, among others: ECMO explantation, need for hemodialysis, stroke, and need for blood transfusions. Results: Low‐flow time was significantly lower in the ECMO+Impella group (60 min vs. 55 min, p = .01). All‐cause mortality was significantly lower in the ECMO+Impella® group (82% vs. 56%, p = .01). The time of circulatory support was shorter in the ECMO cohort (2.0 ± 1.73 vs. 4.76 ± 2.88 p = .05). ECMO decannulation was significantly more feasible in patients with ECMO+Impella® (72% vs. 32%, p = .01). Patients treated with additional Impella® showed significantly more acute kidney injury with the need for dialysis (72% vs. 18%, p ≤ .01). Conclusion: Concomitant Impella® support might positively influence survival and ECMO weaning in eCPR patients. Treatment‐associated complications such as the need for dialysis were more common in this highly selected patient group. Further studies with larger numbers are necessary to evaluate the clinical relevance of concomitant LV‐unloading in eCPR patients using an Impella® device. Abstract : Concomitant impella‐implatation was associated with better survival, higher ECMO weaning rates, but also higher need for blood transfusions, limb ischemia and need for dialysis compared to VA ECMO alone.